2015
DOI: 10.4271/2015-01-0342
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Real-World Energy Impacts of a Thermally Sensitive Powertrain Considering Viscous Losses and Enrichment

Abstract: It is widely understood that cold ambient temperatures increase vehicle fuel consumption due to heat transfer losses, increased friction (increased viscosity lubricants), and enrichment strategies (accelerated catalyst heating). However, relatively little effort has been dedicated to thoroughly quantifying these impacts across a large set of real world drive cycle data and ambient conditions. This work leverages experimental dynamometer vehicle data collected under various drive cycles and ambient conditions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Prior research investigating thermal impacts on vehicle fuel economy involved applying Typical Meteorological Year (TMY) temperature profiles during powertrain simulations [20,21] . Incorporating TMY temperatures was not pursued during this investigation because similar real-world weighted temperature effects can be captured by applying several static ambient temperatures and adjusting for the distribution described by Figure 21.…”
Section: Real-world Simulationsmentioning
confidence: 99%
“…Prior research investigating thermal impacts on vehicle fuel economy involved applying Typical Meteorological Year (TMY) temperature profiles during powertrain simulations [20,21] . Incorporating TMY temperatures was not pursued during this investigation because similar real-world weighted temperature effects can be captured by applying several static ambient temperatures and adjusting for the distribution described by Figure 21.…”
Section: Real-world Simulationsmentioning
confidence: 99%
“…Vehicle modeling in this analysis builds off a previous effort to develop thermally sensitive maps of engine efficiency driven by lumped capacitance models of engine oil, engine coolant, and exhaust catalyst temperature [4]. A schematic of the overall simplified approach is shown in Figure 12.…”
Section: Vehicle Modelingmentioning
confidence: 99%
“…The approach includes backward facing calculations that start with the power required at the wheels which is scaled based on component efficiency for the transaxle, gearbox, torque converter, and engine. In addition to the existing models for thermally sensitive engine efficiency [4], a simplified model of transmission efficiency and its sensitivity to thermal conditions is implemented. As with the thermal models of engine and exhaust temperatures, the transmission oil temperature is modeled using a lumped capacitance approach.…”
Section: Vehicle Modelingmentioning
confidence: 99%
“…Combining the sales-weighted baseline efficiency values, results translate percent into absolute benefit of 1.5 gCO 2 /mi (cars) and 3.2 gCO 2 /mi (light-duty trucks). In previous works that focused on real-world effects on powertrain efficiency [5,7] simplified thermal models of a conventional vehicle were developed from experimental testing data to predict real-world effects on vehicle efficiency. From this work it was shown that regional temperature variations play a significant role in vehicle engine efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The data from this effort were then used to develop a simplified thermally sensitive transmission efficiency model that could be used to investigate transmission warming technology impacts under real world conditions. The goal of this approach is to ultimately integrate all results into an experimentally data derived, simplified model [5,7,8], that allows for analysis of fuel efficiency gains of technologies applied to real world conditions.…”
Section: Introductionmentioning
confidence: 99%